Convections in the Labrador Sea - Davis, Russ E. (2000)
The objective of this grant was to directly observe the vertical velocity, temperature and salinity fields in the Labrador Sea during the wintertime convection season in order to understand the process of water-mass formation and to test and improve numerical models of the process. The effort achieved its technical goals with respect to observations and has generated considerable debate, if not yet understanding, about the processes by which convection brings about change of deep-water masses. A total of 10 Vertical Current Meter floats built under this grant, and 4 from a predecessor grant, were deployed to observe over the winter of 1998. Added to 16 such float deployed the previous year under the predecessor grant and 30 floats prepared by collaborator Breck Owens of Woods Hole Oceanographic Institution, this provide an unprecedented view of the deep convection process. The data is of high quality and the data return was high considering the extreme winter conditions these instruments had to survive.